EFFECT OF ACTIVATION OF THE CONCRETE MATRIX OF TEXTILE-REINFORCED CONCRETE ON ITS PROPERTIES - Shyshkina , О.; Piskun , І. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
There is an increasing focus on replacing traditional steel reinforcement with alternative types that can create lighter structures with enhanced corrosion resistance. One promising option is the use of high-strength textile fabrics, which are made from materials such as glass or carbon fibers. Despite the clear advantages of textile-reinforced concrete structures, several factors hinder their widespread adoption. One major challenge is the significant discrepancy between the strength and deformation characteristics of the concrete matrix and the textile reinforcement. This gap prevents the full realization of the physical and mechanical properties of the reinforcing fabrics. However, modern methods aimed at enhancing the physical and mechanical properties of concrete have emerged. These methods involve using both organic and inorganic substances in ultra-low concentrations as concrete modifiers, improving the overall performance of textile-reinforced concrete. Moreover, contemporary construction emphasizes reducing energy consumption, making the use of binders like slag Portland cement more relevant. Consequently, the primary objective of this research was to investigate how activating the concrete matrix with ultra-small doses of surfactants affects the strength and deformability of textile-reinforced concrete. Concrete samples were prepared using slag Portland cement and various types of textile reinforcement sheets made from glass and carbon rovings. Hydrocarbon was employed as the activator for the concrete matrix. The research determined the relationship between the effectiveness of the activator, indicated by the strength of the concrete, and both the amount of activator used and the type of reinforcing material. The results indicated that bending strength increases with the activation of the concrete matrix for both glass fiber and carbon fiber reinforcement. Additionally, it was found that the effectiveness of the activator diminishes over time.